Bilateral Hippocampal Restricted Diffusion: Same Picture Many Causes. Issue 3 (5th January 2017) - Bhattacharyya, Shamik; Gholipour, Taha; Colorado, Rene A.; Klein, Joshua P.
ABSTRACT: With some regularity, we have encountered the unusual imaging abnormality of bilateral hippocampal restricted diffusion, either in isolation or in combination with other coincident abnormalities. In this retrospective case series, we examine clinical and imaging data to explore potential etiologies and clinical implications of this imaging finding. Sixteen cases with the imaging abnormality are presented, with etiologies including hypoxemia, hypoxemia‐ischemia, and seizures.